2010
DOI: 10.1016/j.freeradbiomed.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to cadmium and arsenic strongly influences concentrations of 8-oxo-7,8-dihydro-2′-deoxyguanosine in urine

Abstract: Exposure to arsenic (As), cadmium (Cd), and lead (Pb) may generate oxidative stress, which can be assessed by 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) in urine, a sensitive marker of oxidatively damaged DNA. We have evaluated oxidative stress induced by chronic mixed exposure to As, Cd, and Pb, as well as the influence of As metabolism and nutritional status, i.e., levels of ferritin (Ft), selenium (Se), zinc (Zn), and manganese (Mn) and body weight. 8-OxodG was measured in urine from 212 women in early p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 46 publications
7
42
2
1
Order By: Relevance
“…The authors suggest that the increase of SOD activity is one of the defence mechanisms of an organism against oxidative stress caused by Cd. Several studies demonstrated that Cd-induced oxidative stress resulted in the generation of 8-OHdG, a reliable marker for oxidative DNA damage 23 39 40. For example, Garçon et al ,23 reported a significant association between 8-OHdG and Cd-U (mean level: 4.67 µg/g creatinine).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the increase of SOD activity is one of the defence mechanisms of an organism against oxidative stress caused by Cd. Several studies demonstrated that Cd-induced oxidative stress resulted in the generation of 8-OHdG, a reliable marker for oxidative DNA damage 23 39 40. For example, Garçon et al ,23 reported a significant association between 8-OHdG and Cd-U (mean level: 4.67 µg/g creatinine).…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, reactive oxygen species (ROS) generated after the exposure are suspected to play a role (Kitchin and Conolly 2010), but researchers have not been able to show direct evidence despite the efforts. Arsenic exposure has been found to induce oxidative DNA damage (ODD) in vitro, in vivo and in epidemiological studies (Engström et al 2010;Sampayo-Reyes et al 2010), and many authors have described that arsenic-associated genotoxicity can be attributed to the generation of ROS (Flora 2011;Hei and Filipic 2004). Lesions in genomic DNA caused by ROS are closely associated with aging and various diseases, including cancer (Kryston et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 8-OH-dG is produced by the hydroxylation of the guanosine moiety of a nucleic acid base, and is an established marker of DNA oxidation (Valavanidis et al, 2009). The production of both isoprostane (Holt et al, 2009; Tomey et al, 2007) and 8-OH-dG (Hong et al, 2013; Sram et al, 2012; Engstrom et al, 2010) may be affected by nutrients that modulate the biological pathways for the generation of free radicals or influence the balance between free radicals and antioxidant capacity in the body. We investigated the role of two antioxidants, vitamin C and zinc, for which dietary intake information was available, on the association between BLL and urinary concentrations of isoprostane, and 8-OH-dG in first-grade children.…”
Section: Introductionmentioning
confidence: 99%